2014
DOI: 10.1002/rcm.6850
|View full text |Cite
|
Sign up to set email alerts
|

Facile Smiles‐type rearrangement in radical cations of N‐acyl arylsulfonamides and analogs

Abstract: The Smiles-type ion fragmentation mechanism is facile for the title compounds, despite the necessity for carbonyl oxygen to serve as a nucleophile. This rearrangement probably occurs in many of the mass spectra reported for structurally similar compounds, in which the nucleophile may be a thione, arylthio, imine, methylene, or methine moiety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Thus, N-alkyl-C-phenylnitrilium cations are the base peaks in the EI spectra of N-alkylsulfabenzamides; 34 it was established that the mechanism involves an ipso attack of the amide oxygen and further fragmentation to the thermodynamically or kinetically favored products. 36 Type a ions were observed in the EI spectra of N-methyl-N-TFA-amphetamines and a four-centered mechanism of oxygen migration has been suggested. 37 The formation of nitrilium ions with a structure of a C-alkyl-N-phenylnitrilium cation have been observed in the electrospray ionization spectra of amides of N-acetylglycine and -alanine, and a mechanism for their formation has been proposed.…”
Section: Resultsmentioning
confidence: 93%
“…Thus, N-alkyl-C-phenylnitrilium cations are the base peaks in the EI spectra of N-alkylsulfabenzamides; 34 it was established that the mechanism involves an ipso attack of the amide oxygen and further fragmentation to the thermodynamically or kinetically favored products. 36 Type a ions were observed in the EI spectra of N-methyl-N-TFA-amphetamines and a four-centered mechanism of oxygen migration has been suggested. 37 The formation of nitrilium ions with a structure of a C-alkyl-N-phenylnitrilium cation have been observed in the electrospray ionization spectra of amides of N-acetylglycine and -alanine, and a mechanism for their formation has been proposed.…”
Section: Resultsmentioning
confidence: 93%
“…1,4-Aryl migration to the carbonyl oxygen instead gave desulfonylated phenols. 43,44 To avert this undesired Smiles rearrangement, we synthesized N-acylsulfonamides bearing tethered alkenes that would rapidly trap the N-centered radical in a 5-exo-trig cyclization. Desulfonylative aryl migration to the incipient alkyl radical would then provide the desired arylethylamine (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism was supported by a heavy atom labeling study and density functional theory calculations . In electron ionization, a fragmentation mechanism of acylarylsulfonamide radical cations has been studied by Irikura and Todua, who concluded that it follows a Smiles-type rearrangement reaction …”
Section: Introductionmentioning
confidence: 99%